2021
DOI: 10.1111/pbi.13529
|View full text |Cite
|
Sign up to set email alerts
|

Wheat heat tolerance is impaired by heightened deletions in the distal end of 4AL chromosomal arm

Abstract: Heat stress (HS) causes substantial damages to worldwide crop production. As a cool season crop, wheat (Triticum aestivum) is sensitive to HS-induced damages. To support the genetic improvement of wheat HS tolerance (HST), we conducted fine mapping of TaHST1, a locus required for maintaining wheat vegetative and reproductive growth under elevated temperatures. TaHST1 was mapped to the distal terminus of 4AL chromosome arm using genetic populations derived from two BC 6 F 6 breeding lines showing tolerance (E60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 87 publications
(106 reference statements)
2
14
0
Order By: Relevance
“…The variation at ELF3 might have occurred because of the positioning of ELF3 within the subtelomeric region (Aguilar and Prieto 2020) which has enhanced levels of recombination which can lead to increased number of sequence and structural variants. This has been observed for other regions, recent studies have reported that a deletion at the distal end of chromosome 4AL is associated with altered heat tolerance (Zhai et al . 2021) and a deletion at the distal end of 5AL encompasses the Rht12 locus which is associated with dwarfing (Sun et al .…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The variation at ELF3 might have occurred because of the positioning of ELF3 within the subtelomeric region (Aguilar and Prieto 2020) which has enhanced levels of recombination which can lead to increased number of sequence and structural variants. This has been observed for other regions, recent studies have reported that a deletion at the distal end of chromosome 4AL is associated with altered heat tolerance (Zhai et al . 2021) and a deletion at the distal end of 5AL encompasses the Rht12 locus which is associated with dwarfing (Sun et al .…”
Section: Discussionsupporting
confidence: 69%
“…The variation at ELF3 might have occurred because of the positioning of ELF3 within the subtelomeric region (56) which has enhanced levels of recombination which can lead to increased number of sequence and structural variants. This has been observed for other regions, recent studies have reported that a deletion at the distal end of chromosome 4AL is associated with altered heat tolerance (57) and a deletion at the distal end of 5AL encompasses the Rht12 locus which is associated with dwarfing (58). Secondly, variation at ELF3 may have been selected by past breeding efforts, leading to a change in allele frequencies, due to advantageous adaptation of flowering time to local climates similar to that seen for selection of Ppd-1 alleles based on latitudinal cline (59) and altitude (60).…”
Section: Wheat Elf3 Might Be a Promising Breeding Targetsupporting
confidence: 67%
“…It is very challenging to isolate the genes responsible for HST in wheat by map-based cloning although heat tolerant mutants were identified 20 years ago ( Mullarkey and Jones, 2000 ). TaHST1 is a QTL that is significantly associated with HST in both vegetative and reproductive stages of wheat ( Zhai et al, 2021 ). It was mapped on the distal terminal of chr4A.…”
Section: Introductionmentioning
confidence: 99%
“…According to reference genome sequence of Chinese spring (CS), this 0.949 Mb region has 19 high confidence genes ( IWGSC, 2018 ). Five markers Xhau1-Xhau5 were used for the detection different haplotypes in this region in wheat cultivars ( Zhai et al, 2021 ). Further investigation revealed that an unusual high number of deletion mutation in this region was observed, which was confirmed by using sequencing data from 10+ wheat genome project.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, emphasis should be placed on sustaining the wheat yields through the identification of tolerant genotypes and promotion of breeding strategies and management practices that can help to build HS resilience and safeguard the wheat production from HS [ 22 ]. An improved understanding of morphological and physiological traits associated with HS tolerance has pragmatic implications for devising countermeasures, e.g., to identify various tolerance mechanisms and their use in alleviation strategies [ 23 , 24 , 25 ]. The mapping of genomic regions governing such physiological traits helped to identify genes (or QTLs) conferring HS tolerance, which serve as a strong base for the marker-assisted (MAS) breeding of HS tolerance in wheat [ 24 , 26 ].…”
Section: Introductionmentioning
confidence: 99%